ANALISIS HAMBATAN PROSES SOSIALISASI NILAI-NILAI ISLAM BAGI REMAJA DALAM KELUARGA (Studi Kasus di Kelurahan Harapan Jaya Kecamatan Sukarame) - Pahril, Danial; Fatimaningsih, Endry (JURNAL SOSIOLOGI, 2012)
As known the family has a strategic role, good or bad family structure can affect both the growth of the childs personality or bad, in this case the socialization process has an important role in the formation of the childs personality through plant values, norms or customs that prevail both within the family and the community. The purpose of this study to clarify the factors inhibiting the process of socialization into the values of Islam to the youth in the family. This study used qualitative methods of data collection techniques through in-depth interviews and literature study, while data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of this study found that the factors inhibiting the process of socialization of Islamic values for adolescents within the family, the first internal factors that condition the parents lack of communication between parents and children and the ability to nurture a child, both the childs condition, such as emotional lability and self-control weak. Then from the first extern factors peers well enough and that both conditions are unfavorable environment.Keywords: the socialization of Islamic values, youth, families